Reflecting on Different Aspects of Classroom Teaching: Mirrors on the Road of Educators’ Self-Professional Development - Alnijres, Batoul Mohammed (Journal of Ecohumanism, 2024)
Nowadays, the topic of teacher professional development (TPD), has attracted a great deal of attention. Professional development aims to help teachers become aware of and learn the different skills and strategies they need to cope with different teaching contexts and situations as well as learners with different needs, interests, and backgrounds. Undoubtedly, reflection can be viewed as a pivotal tool on the road to teachers’ continuous professional development. Reflection is not but a mirror that reflects educators’ practices, shedding light on the positive as well as the negative aspects of the lesson to make informed decisions to address these issues or any other emerging challenges. After combing the literature, the researcher identified some areas where there is much still to be revealed. Therefore, the current study aims to reveal educators’ awareness of reflection and if they are involved in any type of reflection as a means of self-development. The study aims to investigate the different ways (if any) in which in-service language teachers engage with any form of reflection. Finally, the study aims to present teachers’ views on whether pursuing reflection has any positive impact on teachers’ teaching, personality, and practices. Qualitative research was adopted as the method where the aim is to paint a clear picture of participants, their views as well as their practices. Therefore, interviews were implemented and they could successfully result in rich type of data. The data showed that participants resorted to reflecting on the different aspects of their classes. Implications for teachers and stakeholders were made clear whereas suggestions for future research were provided.